Functional features of dispatching control centre for automatic control system of agricultural enterprise - Lytvynov, V.V.; Mykhailiuk, I.V.; Posadska, A.S. (Математичні машини і системи, 2014)
The problems of construction of dispatching control system for agricultural enterprise are investigated. The selection of the functionality of dispatching control subsystem, which allows minimizing losses associated with low-quality and untimely implementation of issues of executive plan is considered in the article. The task of providing timely and qualitative response to unforeseen events is presented Досліджуються проблеми побудови системи оперативного диспетчерського управління для сільськогосподарського підприємства. У статті розглядається вибір функціональності підсистеми оперативного диспетчерського управління, яке дає можливість мінімізувати втрати, пов’язані з несвоєчасним і неякісним виконанням виконавчого плану. Також представлене завдання забезпечення своєчасного та якісного реагування на непередбачені події. Исследуются проблемы построения системы оперативного диспетчерского управления для сельскохозяйственного предприятия. В статье рассматривается выбор функциональности подсистемы оперативного диспетчерского управления, которое позволяет минимизировать потери, связанные с несвоевременным и некачественным выполнением исполнительного плана. Также представлена задача обеспечения своевременного и качественного реагирования на непредвиденные события.